The assessment of soil chemical, physical, and structural properties as landslide predisposing factors in the Serra do Mar mountain range (Caraguatatuba, Brazil) - Cerri, Rodrigo I. [UNESP]; Rosolen, Vania [UNESP]; Reis, Fábio A. G. V. [UNESP]; Filho, Augusto José Pereira; Vemado, Felipe; do Carmo Giordano, Lucilia [UNESP]; Gabelini, Beatriz Marques [UNESP] (Springer Nature, 2020)
Landslides have environmental, social, and economic impact in the Brazilian Atlantic coast (Serra do Mar). In addition to meteorological, geological, and geomorphological settings, mineralogical and pore space heterogeneities in soil covers are considered important characteristics that can influence landslide occurrence. Since soil covers are very clayey, the evaluation of macro- and micromorphological soil features (soil structures, soil materials, and pores) resulted by mass movement during slope instability is difficult. This field of investigation practically does not exist in the Serra do Mar. The objective of this paper is to analyze the soil cover in a toposequence to identify macro- and microscopic soil features resulted from landslide processes, and assess the role of pedogenesis on landslide development. Macro- and micromorphological approaches were used to study the architecture of the soil cover and soil was sampled to determine chemical and mineralogical composition by XRF and XRD. Undisturbed clods were used to determine pore size and pore compartment by mercury porosimetry. It was recognized a brecciated and an undulating parallel-striated fabric. Both features were generated from mass movement and were unclear in the clayey horizons in the bottom of the toposequence. In this level, the occurrence of mottles suggesting short-term soil saturation and the presence of micropores < 1000 nm in soil could be the factors that drive soil movement downslope.
Keywords: Landslide; Serra do Mar; Soil cover; Soil mottles; Weathering profiles